(untitled) (International Journal of Tissue Repair, 2025)
Aims: To evaluate the reduction of wound size in venous leg ulcers (VLUs) after amniotic membrane allograft (AmnioBurgeon (OneBiotech, USA)) treatment. Methods: Single-center retrospective database study of patients treated with an amniotic membrane allograft for VLUs. Wound area was measured prior to each allograft application, and the change in wound area after each application was evaluated over the progression of therapy. Results: In total, 38 patients with 43 VLUs were treated weekly with AmnioBurgeon with an average wound size of 9.4 cm2. During the treatment course, 6% of the wounds completely healed with a mean time to healing of 38.8 days. 46% of the wounds partially healed with at least 50% or greater area reduction within 17.6 days on average. By the 4th week, 42% of wounds achieved 50% or more reduction in their size. Our treatment group included VLUs ranging between 0.25 cm2 and 25 cm2, achieving significant wound area reduction, indicating wound healing trajectory. Conclusion: Amniotic membrane allograft is an effective treatment for VLUs.